Nauczyciel szkoły wyższej i jego kompetencja zawodowa - Vališová , Alena; Svoboda , Petr (Studia Edukacyjne, 2020)
The study includes an overview of key individual teacher’s competencies, their classification and characteristics. The division of competencies is complicated as the individual competencies are interrelated. The substance of the study is a brief definition of the professional competencies of higher-education teachers. The emphasis is placed on the up-to-date teacher’s competencies, about which gives an account a number of definitions of this term in both the contemporary pedagogical and psychological literature. The study also deals with the concept of a professional standard and with digital competencies, the importance of which results from the continual development of the existing scientific disciplines (which already traditionally cooperate with the pedagogy) but also from the development of the newly emerging branches. The digital technologies are nowadays more and more necessary thing both for the normal everyday life and for the occupational one as well. The ability to work with a computer itself is just a marginal matter in today´s conception of the digital competencies. The technologies are constantly developed and the demands on digital competencies are rising. Digital technologies have developed rapidly in the last few years, which has influenced also the sphere of education. New technologies are becoming an important part of education. The reflection of new teaching trends takes place at the intersection of pedagogical, psychological and sociological disciplines. The development is accelerating rapidly due to the ongoing technological changes and innovations. The study is a part of the TAČR (Technological Agency of the Czech Republic) grant project – “Development ofDigital Competencies of Social science Teachers at Secondary Technical Schools”, 02/2018-02/2021PID:TL01000192.